Impact of COVID-19 Pandemic and Lockdown on the Academic Performance and Mental Health of High School Students - Matlin, S Jennifer Ruth; Selvakumar, Y Stanly (Journal of Advanced Research in English & Education, 2022)
COVID-19 pandemic in India is a part of the worldwide pandemic of coronavirus disease 2019 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). COVID-19 has resulted in schools shut all across the world. Research suggests that online learning has been shown to increase retention of information, and take less time, meaning the changes coronavirus has caused might be here to stay. The quality and magnitude of impact on minors are determined by many vulnerability factors like developmental age, educational status, pre-existing mental health condition, being economically underprivileged or being quarantined due to infection or fear of infection. It has been indicated that compared to adults, this pandemic may continue to have increased long-term adverse consequences on children. From this project, we can able to know the exact problems faced by the school-going students during the lockdown period and how it affected their mental health. The significance of this study was to identify and analyse the personal, social and psychological impact of COVID - 19 on the mental health of students and academic performance during the pandemic lockdown. How to cite this article:  Matlin SJR, Kumar YSS. Impact of COVID-19 Pandemic and Lockdown on the Academic Performance and Mental Health of High School Students. J Adv Res Eng & Edu 2022; 7(1): 1-3. DOI: https://doi.org/10.24321/2456.4370.202201